Female Primary Bladder Neck Obstruction: Role of Videourodynamics and Treatment Options in a Rare Clinical Entity. Issue 2 (April 2017) - Ammirati, Enrico; Manassero, Alberto; Giammò, Alessandro; Marson, Francesco; Gurioli, Alberto; Carone, Roberto
Introduction: Primary female bladder neck obstruction is a rare clinical condition characterized by the absence/incomplete bladder neck opening during the voiding phase of micturition. Methods: We present the cases of two women complaining dysuria, abdominal straining and sensation of incomplete bladder emptying. Videourodynamic evaluation was fundamental for a correct diagnosis. Results: Videourodynamic evaluation showed a high detrusor pressure during emptying phase, partial use of abdominal strain, very low urine flow rate and significant postvoid residual; imaging showed a defect in the physiological funneling of the bladder neck, absent or incomplete. The first step therapy is represented by oral alpha-blockers and clean intermittent self-catheterization in case of high postvoid residual. Surgical operations, such as bladder neck incision and resection, represent the last option. Conclusions: In our experience, bladder neck obstruction is a rare condition in women and only a complete clinical evaluation associated with videourodynamic study can lead to an appropriate diagnosis and treatment.